Effects of magainins and cecropins on the sporogonic development of malaria parasites in mosquitoes. - Gwadz, R W (1989)
Magainins and cecropins are families of peptides with broad antimicrobial and antiparasitic activities derived respectively from the skin of frogs or from giant silk moths. In insects, cecropins function as part of an inducible immune system against a number of bacterial infections. When injected into anopheline mosquitoes previously infected with a variety of Plasmodium species, both magainins and cecropins disrupt sporogonic development by aborting the normal development of oocysts; sporozoites are not formed and the vector cannot transmit the parasite to another host. It may be possible to induce effective transmission-blocking immunity in the mosquito vector by the introduction and expression of genes coding for magainins, cecropins, or similarly acting parasiticidal peptides into the mosquito genome.